Transdisciplinary approach to the history and development of complex thought in vocational training - Lugo-Villegas, Ido (2023)
The problem addressed was the decontextualized disciplinary approach of historical sciences and little development of complex thinking in university students. The objective of the investigation was to determine the relationship between the transdisciplinary approach to history and the development of complex thinking in professional training. The methodology of the study is quantitative, with a non-experimental design, correlational level, the analytical-synthetic methods served to generalize and particularize the theoretical and factual information. The sample was made up of 46 students from the Professional School of Historical-Social and Geographic Sciences – Hermilio Valdizán National University. The observation guide was the research instrument. The statistics were used for descriptive and inferential analyses. The results show that the majority of students did not achieve an optimal level in the transdisciplinary approach to history, a similar result in the philosophical, sociological, anthropological, economic, political and educational approach to history. Also, a large part of students did not achieve an optimal level of development of complex thinking, regarding creative thinking, problem solving and critical thinking. In conclusion, transdisciplinary approaches to history and the development of complex ideas have a direct and significant connection with university professional development.